Penggunaan Metode Libqual+Tm untuk Mengukur Kualitas Layanan di UPT Perpustakaan UNP - Aliza, Destia Nur; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discussed about librarians service quality toward users. The librarians of the Library of Padang State University were chosen as an object of a research. Data was collected through questionaires those were given to 40 users who were taken as a sample by using random sampling technique. The data was analized by using the Libqual+TM method. Based on the results of the research, it is concluded that the index score of satisfaction users (IKP) in each dimension of Libqual+TM are: (1) the ability and attitude of librarians in serving (service Affect-sa), in a value of IKP 12%, (2)facilities and atmosphere of the space dimension of the library (library as place-lp), in a value of IKP 13.80%, (3) the instructions and means of access (personal control-pc), in a value of 14.66% IKP, (4) access to information (information access-it) in a value of 13.15% IKP.Keyword: libqual + tm, service.